Bio-oil and biochar derived from the pyrolysis of palm kernel shell for briquette - Nurhayati Abdullahi,; Fauziah Sulaiman,; Safana, Aminu Aliyu (Penerbit Universiti Kebangsaan Malaysia, 2017)
The objective of this study was to produce briquette from the mixture of pyrolysis products. Palm shell was pyrolyzed at a temperature of 400°C for 2 h holding time and heating rate of 10°C/min. The biochar and bio-oil ratio was prepared at 3:1 weight percentages for briquette. The viscosity of bio-oil was improved to increase the bonding forces. The characterization of biochar, bio-oil, coal and briquette were analyzed and presented in this study. The density and compressive strength of briquette were, respectively, found to be 0.94 gcm-3 and 3.20 Nmm-2. The shatter and water resistance of briquette were established to be 97 and 96 wt. %, respectively. The high heating value (HHV) of briquette was 29.6 MJkg-1 greater than that of Malaysian sub-bituminous coal 24.6 MJkg-1. It implies that the briquette produced is stable, durable and qualitative. Therefore, it can be concluded that the briquette can substitute coal in some applications.